Influência do aperto do parafuso na vibração em um processo de torneamento duro - Gibim, Talia Cristina da Silva (Universidade Federal de São Carlos, 2024)
The generation of surfaces with pre-defined textures represents a contemporary objective in the industrial sector. There is a growing demand for the incorporation of surfaces that offer multiple opportunities to optimize component performance, including increased fatigue life, superior wear resistance, reduced friction and improved cooling. Currently, several processes are used to obtain textured surfaces, such as grinding, milling and even vibration-assisted machining. However, it is important to note that all machining processes are intrinsically subject to vibrations, especially when the phenomenon of vibration feedback through the system itself, known as chatter, occurs. This self-excited vibration is generally considered detrimental to tool life and machined surface quality. However, analogously to vibration-assisted machining, it can be assumed that vibration can be beneficially used to create textured surfaces, thus eliminating the need for an external source of vibration. However, controlling and predicting chatter is not a trivial task, several authors have proposed different methodologies and tools seeking to describe the phenomenon, with the stability lobe diagram (DLE) being the most used. The variables that cause the greatest impact on vibration are rotation and feed, but with them alone it is not possible to accurately predict chatter. To control the phenomenon, a deeper study of other factors becomes relevant. Tightening the tool's fixing screw influences the rigidity of the structure and consequently the frequency response. The present work studies the impact of this tightening on the limit cutting depth given by the DLE. The results indicate that with the increase in this torque there is an increase in the limit cutting depth, an increase of 20 N.m of torque caused an increase of 1 mm in the limit depth.
Influence of screw tightening on vibration in a hard turning process
Keywords: Chatter; Diagrama de lóbulos de estabilidade; Torque; Texturização; Torneamento; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO